COMMUNITY EMPOWERMENT AND IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN CILONGOK DISTRICT, BANYUMAS REGENCY IN KARANGLO VILLAGE, CILONGOK DISTRICT, BANYUMAS REGENCY, CENTRAL JAVA PROVINCE - Priyatna, Muhamad; Nugroho, Adam Adi; Rahmat, Sudir (STAI Al-Hidayah Bogor, 2024)
Religious education is crucial in shaping character and morality, yet challenges like limited facilities, a lack of qualified teachers, and low public awareness hinder its quality in Karanglo Village, Cilongok District, Banyumas. Community empowerment emerges as an effective solution to address these issues. This research explores community-driven efforts to improve religious education in Karanglo, aiming to provide recommendations and strategies for strengthening public involvement and enhancing educational effectiveness. Participatory methods are employed, engaging the community in planning, implementing, and evaluating programs. Activities include training, curriculum development, and continuous monitoring to achieve sustainable improvements. These initiatives have positively impacted local religious education, inspiring broader efforts to empower communities and improve education quality in other regions.